Training Counselors Using An Absentee - Cuing System - McClure, W. J.; Vriend, J. (Canadian Journal of Counselling and Psychotherapy, 2012)
The absentee-cuing system investigated in this study refers to the use of a wireless microphone by a counselor trainer to transmit messages to a counselor-in-training while she or he is actually engaged in the act of counseling. The trainer observed the session behind a one-way mirro and coached the trainee with the use of a "bug-in-the-ear" device. Fourteen counseling practicum trainees were exposed to six sessions each using the system for a total of eighty-four sessions. Selected system variables were controlled and studied. The researchers questioned whether abbreviated or extended cues could be used effectively, the extent to which trainer formulation of cues made a difference, whether cue frequency was important, if trainee resistance to or dependency on cues would occur, whether clients would be adversely affected, and if trainers with different supervisory styles could use the system effectively. They concluded that the systemis a rich resource for improving counselor training in every regard.